Įvardžiuotinių būdvardžių kilmė - Valeckienė, Adelė (Baltistica, 1990)
THE ORIGIN OF THE DEFINITE ADJECTIVES The author concludes that the definite adjectives in Baltic and Slavic have evolved from syntactical constructions, identical to the constructions with the same pronoun *i̯o- in Old Indo-Iranian and Greek. Hence these adjectives have roots in the Indo-European period. The original function of the pronoun *i̯o- (with the adjective) was to emphasize, to refer once again, to identify the same object, the way the noun does. The function of the definiteness of these forms is secondary and has developed under the influence of context. In Lithuanian Southern dialects the use of the emphasizing definite adjectives might have been archaic. The forms of numerals and pronouns did not develop the function of definiteness either. They have preserved this emphatic character up to now.